522 Metabolic requisites for T cell protein translation in tumors. (10th December 2020) - Hurst, Katie; Tennant, Megan; Andrews, Alex; Leddy, Lee; Neskey, David; Ball, Lauren; Thaxton, Jessica
Abstract : Background: T cells are a secretory immune subset with the capacity to control solid tumors. Protein translation is of paramount importance in CD8 T cells, controlling proliferation, stimulation and lineage fate. Methods: Herein, we used both the fluorescent analogue of methionine homopropargylglycine (HPG) incorporation assay and O-propargyl-puromycin (OPP) method which enters the A-site of the ribosome and effectively labels and terminates nascent polypeptide chains to monitor protein synthesis in mouse and human tumors. Moreover, we employed label free quantitative proteomics (LFQ), lipidomics, metabolic analysis, and in vivo animal modeling to elucidate mechanisms of protein translation in antitumor immunity. Results: We found that canonical protein synthesis is restricted in endogenous CD8 tumor infiltrating lymphocytes (TILs) by the tumor microenvironment (TME). Proteomic analysis revealed that gluconeogenesis and B-oxidation of fatty acids (FAO) were upregulated in CD8 T cells under tumor stress but these metabolic sources were unable to support translation in the TME. Further, we discovered that glucose metabolism and mammalian target of rapamycin complex 1 (mTORC1) preferentially hinder protein synthesis in CD8 TILs. These data enabled the discovery that proteasomal protein degradation is the optimal source to fuel protein translation in T cells in the stress of solid tumors. We demonstrate that Rapamycin-primed T cells are preferentially powered by proteasomal proteolysis and are able to sustain protein translation in tumors and control tumor growth. Conclusions: Our data establish that canonical protein translation governed by mTORC1 and glucose metabolism is subject to inhibition in the TME and promotion of protein catabolism is a new strategy to support antitumor immunity. Ethics Approval: All animal experiments were in accordance with the MUSC Institutional Animal Care and Use Committee (IACUC), protocol # IACUC-2018-00422 and # IACUC-2018-00347